Tree Selection for Nest of Cattleengret (Bubulcus ibis) in Ketingan Tourisme Village, Sleman Regency, Yogyakarta - Eko Kosasih; Sena Adi Subrata (Jurnal Ilmu Kehutanan)
Habitat selection of Bubulcus ibis in Ketingan Village, Sleman Regency, Yogyakarta was investigated to provide basic information for population management. Presence of Bubulcus ibis nest was surveyed along with identification available tree species. Tree height, canopy size and openness, and distance from human disturbance were also measured for each tree. The Chi Square test showed that bubulcus ibis selected several species as nest trees such as Gnetum gnemon L., Cassia siamea Lamk., Artocarpus heterophyllus Lamk., Calophyllum inophyllum L., Melia azedarach L., Antidesma bunius (L.) Spreng., and Dysoxylum gaudichaudianum(Juss.) Miq. Tree height, canopy height, canopy diameter and the distance from human disturbance showed a significant difference between used and non-used trees for the nest, however diameter breast high (DBH) and canopy openness of trees did not show significant differences. Habitat management of Bubulcus ibis should be improved by controlling its population that needed for the conservation of this bird species.